Molecular players of auxin transport systems: advances in genomic and molecular events*. Issue 1 (1st January 2018) - Mohanta, Tapan Kumar; Bashir, Tufail; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Khan, Abdul Latif; Al-Harrasi, Ahmed Sulaiman
ABSTRACT: Phytohormone auxin plays an indispensable role in the plethora of plant developmental process starting from the cell division, and cell elongation to morphogenesis. Auxins are transported to different parts of the plant by different sophisticated transporter molecules known as 'auxin transporters'.There are four auxin transporter families that have been reported so far in the plant kingdom which includes AUX/LAX (AUXIN-RESISTANT1–LIKES), PIN (PIN-FORMED, auxin efflux carriers), ABCB ((ATP-binding cassette-B (ABCB)/P-glycoprotein (PGP)) and PILS (PIN-Likes). Auxin influx and efflux carriers are distributed in a polar fashion in the plasma membrane whereas ABCB and PILS are present in a non-polar fashion. Other than AUX/LAX, other auxin transporters harbor N-and C-terminal conserved domains along with a variable hydrophilic loop in the transmembrane domain. The AUX/LAX, ABCB and PIN transporters mediate long distance auxin transport whereas PILS and PIN5 protein involved in intracellular auxin homeostasis.